Automated psychological therapy using virtual reality (VR) for patients with persecutory delusions: study protocol for a single-blind parallel-group randomised controlled trial (THRIVE) - Daniel Freeman; Rachel Lister; Felicity Waite; Ly-Mee Yu; Mel Slater; Graham Dunn; David Clark (Trials, 2019)
Abstract Background Persecutory delusions are a major psychiatric problem and are associated with a wide range of adverse outcomes. Our theoretical model views these delusions as unfounded threat beliefs which persist due to defence behaviours (e.g. avoidance) that prevent disconfirmatory evidence being processed. The treatment implications are that patients need to (1) go into feared situations and (2) not use defence behaviours. This enables relearning of safety and hence paranoia diminution. However, this is very difficult for patients due to their severe anxiety. A solution is to use virtual reality (VR) social situations, which are graded in difficulty and which patients find much easier to enter. We have now automated the provision of cognitive therapy within VR using an avatar coach, so that a therapist is not required and the treatment is scalable. In the THRIVE trial, the automated VR cognitive treatment will be tested against a VR control condition. It will contribute to our wider programme of work developing VR for patients with psychosis. Methods Patients with persistent persecutory delusions in the context of non-affective psychosis will be randomised (1:1) to the automated VR cognitive treatment or VR mental relaxation (control condition). Each VR treatment will comprise approximately four sessions of 30 min. Standard care will remain as usual in both groups. Assessments will be carried out at 0, 2, 4 (post treatment), 8, 16, and 24 weeks by a researcher blind to treatment allocation. The primary outcome is degree of conviction in the persecutory delusion (primary endpoint 4 weeks). Effect sizes will be re-established by an interim analysis of 30 patients. If the interim effect size suggests that the treatment is worth pursuing (d > 0.1), then the trial will go on to test 90 patients in total. Secondary outcomes include real world distress, activity levels, suicidal ideation, and quality of life. Mediation will also be tested. All main analyses will follow the intention-to-treat principle. The trial is funded by the Medical Research Council Developmental Pathway Funding Scheme. Discussion The trial will provide the first test of automated cognitive therapy within VR for patients with psychosis. The treatment is potentially highly scalable for treatment services. Trial registration ISRCTN, ISRCTN12497310. Registered on 14 August 2018.